Early emergence of anti‐HCV antibody implicates donor origin in recipients of an HCV‐infected organ. Issue 9 (28th May 2019) - Porrett, Paige M.; Reese, Peter P.; Holzmayer, Vera; Coller, Kelly E.; Kuhns, Mary; Van Deerlin, Vivianna M.; Gentile, Caren; Smith, Jennifer R.; Sicilia, Anna; Woodards, Ashley; McLean, Rhondalyn; Abt, Peter; et al.
Abstract : Hepatitis C virus (HCV) seroconversion among HCV‐uninfected transplant recipients from HCV‐infected (NAT+/Antibody+) or HCV‐exposed (NAT−/Antibody+) donors has been reported. However, the origin of anti‐HCV antibody and the implications of seroconversion remain unknown. We longitudinally tested plasma from HCV‐uninfected kidney (n = 31) or heart transplant recipients (n = 9) of an HCV NAT+ organ for anti‐HCV antibody (both IgG and IgM isotypes). Almost half of all participants had detectable anti‐HCV antibody at any point during follow‐up. The majority of antibody‐positive individuals became positive within 1‐3 days of transplantation, and 6 recipients had detectable antibody on the first day posttransplant. Notably, all anti‐HCV antibody was IgG, even in samples collected posttransplant day 1. Late seroconversion was uncommon (≈20%‐25% of antibody+ recipients). Early antibody persisted over 30 days in kidney recipients, whereas early antibody dropped below detection in 50% of heart recipients within 2 weeks after transplant. Anti‐HCV antibody is common in HCV‐uninfected recipients of an HCV NAT+ organ. The IgG isotype of this antibody and the kinetics of its appearance and durability suggest that anti‐HCV antibody is donor derived and is likely produced by a cellular source. Our data suggest that transfer of donor humoral immunity to a recipient may be much more common than previously appreciated. Abstract : Serologic testing of HCV‐negative transplant recipients who receive an HCV+ organ requires careful interpretation because anti‐HCV IgG, potentially of donor origin, can be detected early after transplantation.